STRATEGIES FOR EFFECTIVE METHODOLOGICAL TRAINING OF ENGLISH LANGUAGE TEACHERS IN THE DIGITAL ERA - Baxtibaeva , Nawbaxar (Наука и инновация, 2025)
This article explores effective strategies for the methodological training of English language teachers in the digital era. The study emphasizes that contemporary teachers require not only linguistic and communicative competence but also the ability to integrate digital pedagogy into their methodological repertoire. An experimental study involving in-service English teachers was conducted to assess the impact of digital strategies such as reflective practice, digital mediation, AI-based feedback, and collaborative online learning. The results indicate that teachers who applied these strategies developed higher levels of adaptability, confidence, and methodological preparedness compared to colleagues trained through traditional approaches. Nevertheless, challenges such as differences in digital literacy, lack of institutional support, and limited resources were identified. The findings highlight the necessity of rethinking teacher education to align with global educational transformations. The article provides practical recommendations for embedding digital tools and reflective methods into teacher training programs. The research contributes to the scientific discourse on digital pedagogy and teacher education by offering a sustainable framework that synthesizes methodological tradition with technological innovation.